Greening the service delivery process in food service sector - Nawang Mustapen, Rosini; Abd Rahman, Azmawani (Human Resource Management Academic Research Society, 2017)
Greening the service sector study has currently increased as service sector become a part of climate change and environmental damage contributor and food service sectors are not exempted. This topic has been debated among scholars and practitioners for over the past 10 years due to increasing of environmental concern. The research in food service operator to date tend to involve the general green practices rather than specific stage process such as the service delivery process, since this process has pertinent connection in service operation. Thus, the purpose of this study is to identify the specific green practices in service process delivery of food service operator and then to review greening service process delivery factors that enhance the greening effort of food service operator through service delivery process. Finally, a conceptual model of the study is proposed.